PELUANG DAN TANTANGAN PROFESI PUSTAKAWAN YANG MELEK INFORMASI DI ERA DISRUPSI: (Sebuah Literature Review) - Zulfikar Ghazali (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
The purpose of this study is to find out how the opportunities and challenges of the librarian profession of information literacy in the era of disruption. This type of research is qualitative with a source of literature review. While this literature review is carried out with four stages consisting of: (a) focus on the discussion to be discussed; (b) linking literature with agree; (c) approve the research and (d) analyze and evaluate the critical literature reviewed based on the research discussion. For research results, in order for the librarian profession to continue to exist and survive and have opportunities in the era of disruption, it can be done in several stages: first, librarians must have competence or expertise in information literacy, second, librarians are required to always develop their potential, one of which is one of them is information literacy skills, third, librarians have the opportunity to become consultants in libraries by having several competencies or abilities such as, skills, knowledge, experience, work attitudes and public trust in the librarian. As for the challenges of the library profession, first, the challenges of adopting attitudes and learning behaviors for life. This is considered a challenge because information literacy implicitly requires an individual to be able to follow new advances in this field (information literacy), secondly, risks arising from failure to understand the concept of relationships related to information literacy, third, the magnitude of the burden and costs involved. high to build and maintain social networks that have been built.